Аналіз стану утилізації теплових і горючих вторинних енергоресурсів та їх використання в комунальній теплоенергетиці промислових вузлів - Kuts G.O.; Litinska L.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2006)
The analysis of yield and using of heat and combustible secondary energy resources in the enterprises of energy-intensive industries. It is proposed the way of its application in heat supply systems in municipal sector of industrial centers.